The Influence of the Use of Polygon-Based Geographic Information Systems on Agricultural Extension Activities in Cirebon Regency - Retno Ayu Ady Tianing Tias; Achmad Faqih; Siti Aisyah (Pusat Publikasi Nusantara, 2026)
This study is motivated by the need to enhance the effectiveness of agricultural extension activities through accurate spatial data utilization. The objective of this research is to examine the influence of polygon-based Geographic Information Systems (GIS) on agricultural extension activities in Cirebon Regency. A quantitative descriptive approach was employed using a survey method involving 64 agricultural extension officers selected through stratified random sampling. The data were analyzed using validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results indicate that polygon-based GIS usage simultaneously has a significant effect on agricultural extension activities, with an R² value of 0.629. Partially, the analytical aspect of GIS shows a positive and significant effect, while the technical, functional, and perceived benefit aspects exhibit positive but insignificant effects. These findings suggest that spatial analytical capability is the most critical factor in improving extension effectiveness. The study concludes that the successful implementation of polygon-based GIS depends not merely on the availability of technology but also on the analytical capacity of extension officers. The implications of this study highlight the importance of strengthening spatial analysis competencies to support data-driven, targeted, and sustainable agricultural extension planning.